Kajian Etnobotani Tanaman Obat Tradisional oleh Masyarakat Kampung Budaya Legok Hayam Desa Girimekar Kecamatan Cilengkrang Kabupaten Bandung (International Forum of Researchers and Lecturers, 2024)
Medicinal plants are plants that are known to contain beneficial compounds that can prevent, alleviate, or cure diseases. Knowledge about medicinal plants has different characteristics depending on the region. This study aims to document the knowledge of residents of the Legok Hayam Cultural Village, Girimekar Village, Bandung Regency about traditional medicinal plants. The ethnobotanical research method was conducted from September 2024 using semi-structured interviews and observations with measurement parameters of Species Use Value (SUV), Family Use Value (FUV), and Fidelity Level (FL). The research sample used a random sampling technique with a total of 25 respondents. The results identified 25 medicinal plants belonging to 15 families, traditional medicinal plants are often obtained by planting in the yard. The most frequently used medicinal plants are ginger, turmeric, binahong and kencur based on their highest utility value. The Zingiberaceae family has the largest contribution to use. In addition, binahong, kencur, katuk, and ginger plants are widely used to treat certain diseases.